2012
DOI: 10.1637/9907-082511-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Application of a Quantitative PCR Assay for Detecting gtxA-Containing Gallibacterium Species in Chickens

Abstract: A quantitative PCR (qPCR) assay using SYBR Green I was developed based on the published sequence of the gtxA gene from Gallibacterium anatis. This method produced reliable specificity, sensitivity, and repeatability. The detection rate of Gallibacterium in 181 clinical samples was 36.5% (66/181) by qPCR, which was superior to the detection rate of Gallibacterium-specific PCR (0/181) and an isolation and identification assay (18.2% or 33/181). No association was found between the prevalence of Gallibacterium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, one previous study showed trans-ovarian transfer at low level [ 41 ], and isolation of G. anatis from the egg yolk has also been observed [ 10 , 11 , 29 , 33 ], both indicating the possibility for vertical transmission. Moreover, quantitative (q) PCR targeting gtxA allowed detection of G. anatis in samples from chickens as young as four days [ 42 ], suggesting that the lack of sensitive methods for identification could have been the reason as to why G. anatis has not previously been detected in chickens younger than four weeks [ 4 ]. The fact that cockerels also seemed to get infected in the reproductive organs and semen suggests that the males potentially may play an important role in transmission between adult birds and possibly to their offspring [ 40 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…However, one previous study showed trans-ovarian transfer at low level [ 41 ], and isolation of G. anatis from the egg yolk has also been observed [ 10 , 11 , 29 , 33 ], both indicating the possibility for vertical transmission. Moreover, quantitative (q) PCR targeting gtxA allowed detection of G. anatis in samples from chickens as young as four days [ 42 ], suggesting that the lack of sensitive methods for identification could have been the reason as to why G. anatis has not previously been detected in chickens younger than four weeks [ 4 ]. The fact that cockerels also seemed to get infected in the reproductive organs and semen suggests that the males potentially may play an important role in transmission between adult birds and possibly to their offspring [ 40 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Moreover, in American countries, i.e., the USA (Shaw et al 1990 ; Zellner et al 2004 ; Jones et al 2013 ), Canada (Shapiro et al 2013 ), Mexico (Vazquez et al 2003 ; Bojesen et al 2007a , 2008 ; Chavez et al 2017b ), and Peru (Mendoza et al 2014 ), cases of G. anatis were recorded. In addition, Gallibacterium have been recorded in Australia (Gilchrist, 1963 ), some African countries, such as Nigeria (Addo and Mohan, 1985 ; Lawal et al 2017 ), Egypt (Elbestawy, 2014 ; Sorour et al 2015 ; Abd El-Hamid et al 2016 , 2018 ; Mataried, 2016 ; Elbestawy et al 2018 ; Elewa, 2021 ; Algammal et al 2022a ), and Morocco (Nassik et al 2019 ), and many Asian counties, i.e., Japan (Suzuki et al 1996 ; Huangfu et al 2012 ; Zhang et al 2017 ), Taiwan (Lin et al 2001 ), China (Chuan-qing et al 2008 ; Guo, 2011 ), India (Singh, 2016 ; Singh et al 2016 , 2018 ), Iran (Ataei et al 2017 , 2019 ; Allahghadry et al 2021 ), Turkey (Yaman and Sahan 2019 ), and Syria (Janetschke and Risk 1970 ). The incidence of G. anatis infection in various parts of the world is depicted in Table 1 .…”
Section: Historymentioning
confidence: 99%
“…Furthermore, some G. anatis infections in humans have been detected (Aubin et al 2013 ; Driessche et al 2020 ). Regarding age susceptibility, older research studies have reported that young birds are less susceptible to G. anatis than adults (Bisgaard 1977 ; Mushin et al 1980 ), whereas Huangfu et al ( 2012 ) informed an extreme rate of detection and isolation of G. anatis from chickens aged 5–6, 12, 18, and 55–58 weeks. However, G. anatis was isolated from broiler chickens (Abd El-Hamid et al 2016 ).…”
Section: Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, G. anatis has been studied as an opportunistic pathogen that can colonize chickens at 4 days of age and persist until they grow into laying hens ( Huangfu et al, 2012 ). The detrimental effects of this genus on chicken breeding have enhanced its importance as an economic risk, and hence, specific tests to unequivocally identify Gallibacterium species have been sought and reported ( Bojesen and Shivaprasad, 2007 ; Alispahic et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%